2013
DOI: 10.1007/s13337-013-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient immunodiagnosis of Large cardamom chirke virus using the polyclonal antiserum against Escherichia coli expressed recombinant coat protein

Abstract: Large cardamom chirke virus (LCCV), genus Macluravirus, family Potyviridae is an important constrain in large cardamom production in India. Purification of LCCV from large cardamom tissues is difficult and therefore immunodiagnostic reagents are not available. In the present study, we have successfully expressed coat protein (CP) gene of LCCV in Escherichia coli. The purification of expressed protein by Ni-NTA affinity chromatography was inefficient due to precipitation of protein during renaturation. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The supernatant containing protein was collected and the step was repeated for 2-3 times to remove SDS. Finally, the protein was dialyzed against Milli-Q water for 12 h at 4 °C (Vijayanandraj et al 2013).…”
Section: In Vitro Expression and Purificationmentioning
confidence: 99%
“…The supernatant containing protein was collected and the step was repeated for 2-3 times to remove SDS. Finally, the protein was dialyzed against Milli-Q water for 12 h at 4 °C (Vijayanandraj et al 2013).…”
Section: In Vitro Expression and Purificationmentioning
confidence: 99%
“…Large cardamom chirke virus, a member of the genus Macluravirus in the family Potyviridae , which naturally infects large cardamom was recorded to infect C. annuum (landrace Dalle Khursani), a solanaceous crop, for the first time, exhibiting the cross-species transmission capability of macluraviruses [ 21 , 41 ]. The LCCV, a positive sense single stranded RNA virus, is vectored by aphids, Rhopalosiphum maidis , Brachycaudus helichrysi , and Myzus persicae in a non-persistent manner [ 42 , 43 ]. Its natural cross-transmission to chilli has raised concerns over a possible new outbreak in solanaceous crops.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous production of polyclonal antibodies (PAb) to virus using purified preparation is difficult and considered as a major limitation in immunodiagnosis. To overcome this problem, the viral capsid protein is expressed as a recombinant fusion protein and used as an antigen for raising PAb to a number of plant viruses (Rani et al 2010;Khatabi et al 2012;Tatineni et al 2013;Vijayanandraj et al 2013). Recently, Sharma et al (2014) identified a putative coat protein gene of BSMYV based on in silico analysis and developed recombinant antibodies for detecting the virus from leaf samples having typical streak symptoms.…”
Section: Introductionmentioning
confidence: 99%